Evaluation of nerve function by source estimation based on anatomical location of brachial plexus - Hashimoto, Jun; Kawabata, Shigenori; Okawa, Atsushi; Watanabe, Taishi; Ishida, Koki (Transactions of Japanese Society for Medical and Biological Engineering, 2021)
Introduction: Magnetoneurogram recording of the brachial plexus (BP) in the prone position requires some burden on subjects. We report on the visualization and consistently evaluation of nerve activity in the BP and cervical spinal cord in the supine position.Method: Magnetoneurogram of 3 healthy volunteers were measured around the surface of the posterior neck after median nerve stimulation. After magnetoneurogram recording, evoked action currents were computationally reconstructed and visualized by a spatial filter method in the area that was set reflected anatomically position of BP. Imaginary electrode were set along action current pathway and then calculated current waveforms.Result: In all cases, we successfully visualized action currents of BP and cervical spinal cord in the supine position. Reconstructed action currents flowed into the intervertebral foramina and traveled cranially along the spinal canal.Conclusion: We proposed evaluation method in BP and cervical spinal cord in supine position with less burden.